2020
DOI: 10.2147/dmso.s263883
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circulating miR-15a and miR-222 as Potential Biomarkers of Type 2 Diabetes</p>

Abstract: Background: In recent years, considerable attention has been paid to the role of microRNAs (miRs) as biomarkers in type 2 diabetes (T2D). The aim of the study was to evaluate the expression levels of miR-15a and miR-222 in diabetic, pre-diabetic, and healthy individuals. Materials and Methods: Ninety individuals, who were referred to the Yazd diabetic center, were enrolled in this study and then classified into three groups as healthy, pre-T2D, and diabetic based on the clinical manifestations. Real-time PCR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Our results indicated that TC and miR-222-3p acted as the independent risk factors for CVD in PCOS non-ow patients. The deregulation of miR-222 expression is implicated in a series of DM and CVD [ 32 , 33 ]. Collectively, high expression of miR-222-3p was correlated with increased risks of diabetic and cardiovascular diseases in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that TC and miR-222-3p acted as the independent risk factors for CVD in PCOS non-ow patients. The deregulation of miR-222 expression is implicated in a series of DM and CVD [ 32 , 33 ]. Collectively, high expression of miR-222-3p was correlated with increased risks of diabetic and cardiovascular diseases in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the selected miRNAs, miR-15-5p, miR-375-3p and miR-21-5p are associated to insulin production in pancreatic β-cells. A significant downregulation of miR-15a-5p has been demonstrated in pre-diabetes and T2D, representing a useful tools to predict the onset of the disease and to differentiate subjects with alteration of glycemic metabolism from healthy controls [51]. Moreover, plasma levels of miR-15a-5p correlate with disease severity [52].…”
Section: Discussionmentioning
confidence: 99%
“…Still, there are some papers describing miRNA levels in plasma or in the heart tissue of individuals suffering from MetS or T2D, which might reflect microenvironmental influence on macrophage content. For example, some authors described downregulation of miR-126, miR-15a, miR-29b, and miR-223 in the plasma of diabetic patients, of patients with CAD, and of Lep ob mice [ 36 , 37 ], whereas He et al observed downregulation of miR-21 in the serum of patients with MetS and in circulating monocytes of type 1 diabetic individuals [ 38 ]. These observations of miRNA levels in sera are in line with our data regarding cardiac macrophages.…”
Section: Discussionmentioning
confidence: 99%